The experience of female veterans and health seeking behaviors - Switzer, Jennifer (Kansas State University, 2022)
Most military branches began to allow females to serve equally alongside males in the 1940’s. However, militarized masculinity poses a challenge for female service members as they negotiate military norms that continue as they transition to civilian life. Health services provided by the military are aimed to help with deal with life and work challenges. However, it is unclear female service members utilize these services as they are intended. The purpose of this study was to provide a better understanding of how health services were utilized by female Army Veterans based on their personal experiences during military service. The study focused on how these experiences have impacted the decision-making process to seek health services during and/or after service. A phenomenological heuristic qualitative study with 11 female Veterans (M =120 months; Service Range =36 months-328 months) with an overall average of 10 years of Active Army Service was conducted using a semi-structured interview guide. The study elicited participants’ experience with health services offered by the military. Cross-thematic analysis found several themes that prevented participants from accessing health services during active duty: experiences of sexism, sexual harassment, unsupportive leadership, challenges of physical health, and limited access to social, family and health resources. The Vulnerability, Stress and Adaptation model was used to conceptualize the study and make meaning of the findings. Clinical and research implications are discussed.
Keywords: Female; Veteran; Healthcare; Experiences; Army